2021
DOI: 10.1007/s42242-020-00116-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of conductive 3D printed PCL/MWCNTs scaffolds with electrical stimulation for bone tissue engineering

Abstract: Critical bone defects are considered one of the major clinical challenges in reconstructive bone surgery. The combination of 3D printed conductive scaffolds and exogenous electrical stimulation (ES) is a potential favorable approach for bone tissue repair. In this study, 3D conductive scaffolds made with biocompatible and biodegradable polycaprolactone (PCL) and multi-walled carbon nanotubes (MWCNTs) were produced using the extrusion-based additive manufacturing to treat large calvary bone defects in rats. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 54 publications
4
47
0
Order By: Relevance
“…However, poor administration of growth factors (i.e., uncontrolled release from scaffolds) can lead to ectopic bone growth [ 114 ]. Alternatively, recent studies have shown that biophysical cues, particularly scaffold conductivity, in conjunction with electrical stimulation (ES) can better aid in the generation of healthy bone tissue without the need for additional growth factors [ 18 , 115 ]. Furthermore, by employing stimuli-responsive (i.e., piezoelectric) materials as scaffolds for BTE applications, cells can convert scaffold generated stimuli into biochemical signals that illicit changes to other cellular signaling events, potentially providing scaffolds that closely approximate natural bone tissue.…”
Section: Bone Tissue Engineering: Cells Materials and Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, poor administration of growth factors (i.e., uncontrolled release from scaffolds) can lead to ectopic bone growth [ 114 ]. Alternatively, recent studies have shown that biophysical cues, particularly scaffold conductivity, in conjunction with electrical stimulation (ES) can better aid in the generation of healthy bone tissue without the need for additional growth factors [ 18 , 115 ]. Furthermore, by employing stimuli-responsive (i.e., piezoelectric) materials as scaffolds for BTE applications, cells can convert scaffold generated stimuli into biochemical signals that illicit changes to other cellular signaling events, potentially providing scaffolds that closely approximate natural bone tissue.…”
Section: Bone Tissue Engineering: Cells Materials and Cuesmentioning
confidence: 99%
“…These conductive scaffolds can then be divided into two distinct categories based on their composition, conductive polymer-based scaffolds and conductive nanomaterial-based scaffolds. Conductive bone scaffolds have the ability to transfer both electrical and electromechanical signals directly to targeted cells; showing the ability to improve proliferation and osteogenic differentiation in vitro, as well as bone formation in vivo, as presented in several studies [ 22 , 77 , 104 , 115 , 138 ]. Through this, conductive scaffolds can be seen as a way to not only decrease healing times associated with traumatic injuries, but also improve tissue repair overall.…”
Section: Conductive Materials and Strategies For Induced Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The tartrate-resistant acid phosphatase positive cell formation was promoted. While the osteoclastogenesis was inhibited using MWCNTs, the use of ES promoted it [133]. Similarly, a 3D printed porous scaffold with aligned MWCNTs and nHA was prepared by Huang et al [134].…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…[ 3 ] Large bone defects require bone fixation through autografts or allografts for complete healing to be achieved. [ 4,5 ] The autografts and allografts techniques are considered to be a gold‐standard treatment for large bone defects but they suffer from limitations such as multiple surgeries, potential morbidity, immunogenic responses, infection, and pathogen transmissions. [ 6 ] Bone tissue engineering emerged as an alternative approach and efficient methodology to heal, repair, and reconstruct large bone defects and tissues, and has generated substantial development in bone‐regeneration thus eliminating the drawbacks pertaining to autografts and allografts.…”
Section: Introductionmentioning
confidence: 99%